Inside Front Cover: CRISPR‐Cas system for biomedical diagnostic platforms (View 3/2020). Issue 3 (22nd September 2020) - Wang, Zhen; Cui, Wenguo
Abstract : In article number 20200008, Wenguo cui and co‐workers demonstrate clustered short palindrome repeats with regular intervals, abbreviated as CRISPR, functions as a self‐defense system for prokaryotes, detecting particular pathogenic nucleic acid, interfering with the functions of exoteric DNA and protecting them against foreign invaders. The CRISPR‐Cas system is a prokaryotic immune system that confers resistance to foreign genetic elements such as those present within plasmids and phages that provides a form of acquired immunity. RNA harboring the spacer sequence helps Cas (CRISPR‐associated) proteins recognize and cut foreign pathogenic DNA. Pathogens especially with the characteristic of infection have become one of serve diseases which threatens people with health and living quality in metropolis like Shanghai, a world‐famous cosmopolitan city. Over the last two decades, remarkable achievement has been made considering the development of CRISPR‐Cas system based diagnostic methods and engineering these modules to suit or enable various pathogens detection. All told, it opened a new window in the clinical laboratory with remarkable convenience, sensitivity and specificity, and has the potential for not only pathogen detection during daily practice or pandemic, such as novel coronavirus disease outbreak in 2019, but also cancer and genetic diseases.